Opportunities and Challenges for Sustainable Bioremediation of Natural and Synthetic Estrogens as Emerging Water Contaminants Using Bacteria, Fungi, and Algae - Anisa, Ratnasari; Achmad, Syafiuddin; Ahmad Kueh, Beng Hong; Suhartono, Suhartono; Tony, Hadibarata (Springer Nature Switzerland AG, 2021)
The occurrence of newly emerging contaminants such as estrogens in water environment has the potential negative effects to human health as well as the surrounding wildlife. This demands efficient approaches for their removals from the water environment. Among all feasible solutions, biodegradation shows promising prospects to remediate estrogens from the environment since it is relatively economical and environmentally friendly compared to chemical and physical treatment approaches. To offer coverage on the present advances of this technology, this paper critically reviews the opportunities and challenges for bioremediation of estrogens using bacteria, fungi, and algae. In general, the capabilities to remove estrogens from water environments by bacteria, fungi, and algae have been highlighted and discussed. Additionally, several advantages and disadvantages are recognized before they are implemented widely in full-scale treatments. Moreover, a comprehensive discussion on the transformation of estrogens using these organisms is also presented, showing vividly that estrogens can be transformed into less toxic chemicals. The review ends by offering several prospective areas for expansion in the future specifically in focusing on the evaluation of other available microorganisms that can survive under numerous hostile environmental conditions, since, in the real application, complex mixtures and extreme environmental conditions are commonly observed particularly in the wastewater treatment systems.